2016
DOI: 10.1080/15563650.2016.1214275
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-based recommendations on the use of intravenous lipid emulsion therapy in poisoning

Abstract: Background: Although intravenous lipid emulsion (ILE) was first used to treat life-threatening local anesthetic (LA) toxicity, its use has expanded to include both non-local anesthetic (non-LA) poisoning and less severe manifestations of toxicity. A collaborative workgroup appraised the literature and provides evidence-based recommendations for the use of ILE in poisoning. Methods: Following a systematic review of the literature, data were summarized in four publications: LA and non-LA poisoning efficacy, adve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
112
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(118 citation statements)
references
References 66 publications
1
112
0
5
Order By: Relevance
“…The propofol infusion that this patient received delivered 10–40 mg/kg/hour of ILE for 16 hours. This is in the region of half the recommended dose of 50 mg/kg/hour (or 0.25 mL/kg/hour of 20% ILE) 5. Following the relapse and repeat bolus, an infusion of ILE was started and continued for 14 hours, after which time the patient remained stable.…”
Section: Discussionmentioning
confidence: 99%
“…The propofol infusion that this patient received delivered 10–40 mg/kg/hour of ILE for 16 hours. This is in the region of half the recommended dose of 50 mg/kg/hour (or 0.25 mL/kg/hour of 20% ILE) 5. Following the relapse and repeat bolus, an infusion of ILE was started and continued for 14 hours, after which time the patient remained stable.…”
Section: Discussionmentioning
confidence: 99%
“…Recommended dosing regimen is a 1.5 mL/kg bolus over 2‐3 minutes followed by a continuous rate infusion at a rate of 0.25 mL/kg/min over 1 hour. In human patients, it is suggested that ILE doses should be limited to a maximum of 10% of the total blood volume to avoid lipid overload and limit possible complications arising from increased triglyceride concentrations . The dose chosen in this patient was similar to the recommended dose listed in the position statement from the ACMT on ILE.…”
Section: Discussionmentioning
confidence: 99%
“…In human patients, it is suggested that ILE doses should be limited to a maximum of 10% of the total blood volume to avoid lipid overload and limit possible complications arising from increased triglyceride concentrations. 25 The dose chosen in this patient was similar to the recommended dose listed in the position statement from the ACMT on ILE. At the author's institution, repeat doses are given every 2-6 hours based upon the persistence of clinical signs, as well as the presence of lipemia within the serum.…”
Section: Discussionmentioning
confidence: 99%
“…The workgroup emphasizes that dose-finding and controlled studies reflecting human poisoning scenarios are required to advance knowledge of limitations, indications, adverse effects, effectiveness, and best regimen for ILE treatment [49].…”
Section: Blood-brain Barriermentioning
confidence: 99%